Application of axiomatic design to the toaster design - a case study - Nazril bin, Mohd Najib (University Malaysia Sarawak, UNIMAS., 2004)
This project is preliminary project on application of axiomatic design concept to toaster design case study. The main objectives of the project are to understand and able to use the Accalaro Designer version 2, improve the quality of functional of the product and to design the product by using the axiomatic design theory.